Trust Ties between Entrepreneurs and the State - Silveira-Pérez, Yahilina (2015)
This work is based specifically on determining these bonds of trust between entrepreneurs and state agencies. The methodology is applied to a sample Business sector Ubá furniture, region of Minas Gerais, Brazil. According to the theoretical foundations of enterprises, they are an essential source of employment in the economic development of the regions. Not only encourage self-employment but also provides new opportunities to employ others. In this sense, the entrepreneur is a person with a high sense to take risks in terms of advantage innovative opportunities. Moreover, it is at this stage where it is considered that the management of trust plays a key role among its features. Trust yourself, other people and institutions, can be a key element in the success of their activities. The methodology was applied through a structured questionnaire determined using factor analysis and linear regression analysis using SPSS 20.0, which in the case study of entrepreneurs furniture Ubá, support laws no positive impact on government bonds of trust of entrepreneurs in state agencies that represent or trust relationships. Nevertheless, entrepreneurs who succeed in establishing trust with state agencies have increased integration and satisfaction with their relationships.